Urinary kallikrein activity of workers exposed to lead. - Boscolo, P (1978)
Two groups of men of different age ranges and with the same period of lead exposure were selected for study in a recently opened car-battery factory. Two other groups of age-matched men, not exposed to heavy metals in their work, were used as controls. Morning urines were collected from control and exposed groups for determination of urinary kallikrein activity, urinary delta-amino-levulinic acid (ALA) and lead levels. The environmental lead levels and the urinary ALA and lead values indicated that exposure in the factory was not heavy. The older group of lead-exposed workers showed greatly reduced urinary kallikrein activity compared with that of the age-matched controls. In contrast, the younger group did not show any significant alteration in urinary kallikrein excretion.